Behavior and influence mechanisms of enterprises using government subsidies: evidence from China - Yan, Xiaochang; Huang, Guitian (Technological and Economic Development of Economy, 2021)
This study investigates the effects of different subsidy use patterns on economic performance, the effect mechanisms, and differences among enterprises with heterogeneous economic performance. A theoretical model is built to analyze the factors influencing subsidy use. Applying ordinary least squares and panel quantile regressions on panel data of China’s 3,565 A-share listed companies from 2007 to 2017, we find that subsidies can significantly improve economic performance. Specifically, enterprises usually use subsidies in three different ways (i.e. R&D input, expansion of production capacity for existing products, and human resource training), and the positive impact of these three use patterns on economic performance is moderated by two factors (i.e. the proportions of both R&D operating expenses and human resource training cost) in different degrees. Moreover, the effects are more significant in the lower quantile of economic performance; hence, heterogeneity of economic performance must be considered when formulating relevant policies.First published online 24 August 2021